Singlet fission in organic crystals : ultrafast spectroscopic study - Ma, Lin (2014)
Singlet fission (SF) is a spin-allowed process in which one singlet excited molecule shares its energy with an adjacent molecule in the ground state, both molecules forming a pair of triplet states. It has attracted an increasing interest in recent years due to its potential to improve the efficiency of organic solar cells. In this thesis, singlet fission in organic crystals was studied by use of ultrafast spectroscopic techniques. We studied the one-photon-induced SF in two kinds of organic crystals, i.e., the monomeric rubrene and dimeric alpha-perylene. SF in both crystals occurs via direct coupling between the excited singlet states and triplet pair states. For the first time, we observed the two-photon induced SF, and demonstrated that SF rate does not depend on the symmetry of excited state. The origin of rubrene fluorescence is explained in terms of interplay between SF and energy trapping.